Rahmatullah Bukhari and the Contemporary Significance of His Ethical Views - Saodat Abdullaeva (CV. Media Digital Publikasi Indonesia, 2026)
The article provides a philosophical analysis of the life, scholarly and literary activity, and ethical views of Rahmatullah Bukhari (Vazeh), a prominent representative of the scholarly and literary environment of nineteenth-century Bukhara. Although the thinker did not compose a separate ethical treatise, the ideas advanced in his tazkira